2010
DOI: 10.1179/136485910x12647085215615
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological studies on the cutaneous leishmaniasis caused byLeishmania(Leishmania)donovaniin Sri Lanka

Abstract: Sri Lanka is the newest reported focus of human leishmaniasis within the Indian subcontinent. Over the last 8 years, more than 2000 cases of cutaneous leishmaniasis (CL), apparently caused by Leishmania donovani (a species usually associated with the visceral form of the disease), have been passively identified in the country. The clinical profiles of 401 suspected cases of CL in Sri Lanka were recently explored and some of the cases' immunological responses were investigated, in antibody-detection assays base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 16 publications
5
57
2
Order By: Relevance
“…Although it had been reported that outdoor occupation is a risk factor for CL in the northern area of Sri Lanka, 24 our findings do not show such an association. The previous study reported an odds ratio of 6.5 to have CL among armed forces personnel who have significant exposure to forest areas compared with unemployed adults.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…Although it had been reported that outdoor occupation is a risk factor for CL in the northern area of Sri Lanka, 24 our findings do not show such an association. The previous study reported an odds ratio of 6.5 to have CL among armed forces personnel who have significant exposure to forest areas compared with unemployed adults.…”
Section: Discussioncontrasting
confidence: 55%
“…This finding is consistent with observations made in other highly endemic districts in Sri Lanka. 24 Living at the edge of paddy fields was the only identified risk factor for development of leishmaniasis in this study.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations